A Critical Discourse Analysis on Teachers’ Verbal Feedback Patterns in EFL CLT Classrooms: Analisis Wacana Kritis pada Pola Umpan Balik Verbal Guru di Kelas EFL CLT - Dabiri, Asma (JEES (Journal of English Educators Society), 2018)
As providing feedback can have an effective role for the learning process, this study with a critical discourse analysis point of view in social scientific research investigated feedback patterns of four English language teachers on learners’ responses in four English Language institutes with Communicative Language Teaching (CLT) approach toward teaching and learning. In doing so, the classes were observed. The interactions were audio-taped and transcribed. The findings revealed that in providing feedback to learners, teachers gave positive feedback (approving and repetition), interactional feedback and corrective (negative feedback) in classrooms. Positive feedback as approving and repetition were the most type of feedback which the teachers made use of. The findings provide insights into feedback patterns in an EFL context and consequently they set up an argument to critically assess one of the most fundamental principles of CLT approach which is giving positive feedback to learners. Attention should be directed to EFL teachers’ ideologies in providing feedback to the students to uncover their philosophy of teaching and learning as a clue to detect their criteria in choosing some habits of providing feedback than others and hence to expand this area further.